Analisis Pengaruh Disiplin Kerja Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Abad Selatan Kabupaten Alor - Moumalai, Frannikson; Gorang, Alvonso Fanisius; Peny, Theresia Lounggina Luisa; Hermayanti, Hermayanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
Performance is the result or level of success of a person as a whole during a certain period in carrying out tasks compared to work standards, targets or goals or criteria that have been determined in advance and have been mutually agreed upon. So far, in carrying out their duties, employees of the South Century District Office of Alor Regency still need to pay attention to optimal performance so that it has an impact on achieving the objectives of the South Century District Office of Alor Regency. For this reason, it is necessary to pay attention to the factors of work discipline, work environment and work motivation. This study aims to determine the effect of work discipline, work environment and work motivation on employee performance at the South Century District Office, Alor Regency. either partially or simultaneously. The respondents of this research were 21 employees. Data collection using questionnaires, observation, and documentation studies. The data is then analyzed using the t-test to determine the partial effect and the F-test to determine the simultaneous effect on performance with the results of the study being: The variables of work discipline, work environment, work motivation and employee performance have a Pearson product moment correlation value which is above the limit of 0.3 for the validity test. The variables of work discipline, work environment, work motivation and performance have a chronbah alpha value which is above the limit of 0.6 for the reliability test. The variables of work discipline, work environment, work motivation and employee performance have a test value for each classic assumption test that is above alpha and passes the classic assumption test. There is an influence of Work Discipline on Employee Performance in the South Abad sub-district office, Alor Regency, as evidenced by the significance value of the t test, which is 0.001, which is smaller than the research alpha value, which is 5% (0.05) There is an influence of the work environment on employee performance in the South Abad sub-district office, Alor Regency, as evidenced by the significance value of the t test, which is 0.001, which is smaller than the research alpha value, which is 5% (0.05) There is an effect of work motivation on employee performance in the South Abad sub-district office, Alor Regency, as evidenced by the significance value of the t test, which is 0.003, which is smaller than the alpha value of the study, which is 5% (0.05) There is an influence of work discipline, work environment and work motivation on employee performance in the South Century District Office of Alor Regency, as evidenced by the significance value of the F test which is 0.000 which is smaller than the research alpha value of 5% (0.05) From the results of the research and the conclusions of the research, the research team suggested to Respondents (sub-district employees of the south century) that employees are expected to be able to maintain the performance of employees who have been well organized to date, while continuing to improve themselves given the various changes in work situations during a pandemic like what happened At the moment. Suggestions are also given to the sub-district head of the southern century of Alor Regency, so that the leaders who have nurtured and built the values ​​of work discipline and a work environment that are well ingrained in this scope of work can be maintained and by continuing to provide enthusiasm, motivation for the development of much better employee performance and overall job performance.